Integration Of Computational Thinking In Mathematics Learning In Senior Secondary Education From 2019-2023: Systematic Literature Review - Martini, Martini; Aminah, Neneng (Pattimura University, 2024)
Mathematical thinking is very important for everyone and must be trained from childhood to face and solve everyday problems. To overcome problems and adapt to changes that occur in the era of globalization, changes in the industrial revolution 4.0 The world of education must be able to act quickly and precisely. Computational Thinking (CT), also known as computational thinking, is a process that involves formulating problems and finding solutions, as well as using these solutions to process information effectively to solve problems. The first objective, of this research it is hoped that someone will find it easy to observe problems, find solutions to problems, solve problems, and be able to develop solutions or solutions to problems. Apart from that, computational thinking hones us to think more effectively and efficiently. Second, to obtain a theoretical framework that can help solve the problem being researched to reveal concepts relevant to the case, especially in research that studies more deeply about research.Integration of Computational Thinking in Mathematics Learning in Senior Secondary Education. Stages In this research there are five stages, formulating the problem (1), searching for literature (2), selecting appropriate literature search results (3), analyzing several literature from test results (4), and making conclusions (5). The results show that articles reviewed by researchers regarding Computational thinking are associated with technology namely, from 14 articles referring to 9 articles that passed QA.